Viable Severe Acute Respiratory Syndrome Coronavirus 2 Isolates Exhibit Higher Correlation With Rapid Antigen Assays Than Subgenomic RNA or Genomic RNA - Tariq, Misbah; Kim, Dong-Min; Kim, Choon-Mee; Bang, Mi-Seon; Lee, You Mi; Seo, Jun-Won; Kim, Da Young; Yun, Na Ra (Frontiers in Microbiology, 2021)
Background: Rapid identification and effective isolation are crucial for curbing the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). To meet this requirement, antigen-detection rapid diagnostic tests (Ag-RDTs) are essential. Methods: Between February 2020 and August 2020 we performed a cohort study of patients with confirmed COVID-19. The clinical performance of Ag rapid fluorescence immunoassay (FIA) and Ag Gold was evaluated and compared in parallel with genomic and subgenomic real-time reverse transcription-polymerase chain reaction (rRT-PCR) and cell culture-based assays. Results: In total, 150 samples were tested. Of these, 63 serial samples were obtained from 11 patients with SARS-CoV-2 and 87 from negative controls. . Serial respiratory samples were obtained 2 days prior to symptom onset (−2) up to 25 days post symptom onset. Overall, for rRT-PCR-positive samples (n = 51), the detection sensitivity of Ag rapid FIA and Ag Gold was 74.51% and 53.49%, respectively, with a specificity of 100%; however, for samples with low cycle threshold (Ct) values, Ag rapid FIA and Ag Gold exhibited a sensitivity of 82.61% (Ct ≤ 30, 5.6 log10RNA copies/mL) and 80% (Ct ≤ 25, 6.9 log10RNA copies/mL), respectively. Despite low analytical sensitivity, both Ag-RDTs detected 100% infection in cell culture-positive samples (n = 15) and were highly effective in distinguishing viable samples from those with subgenomic RNA (66.66%). For both Ag-RDTs, all samples that yielded discordant results (rRT-PCR +ve/Ag-RDT −ve) were also negative by culture. Conclusion: The data suggest that Ag-RDTs reliably detect viable SARS-CoV-2; thus, they may serve as an important tool for rapid detection of potentially infected individuals.